2010
DOI: 10.1186/1471-2164-11-236
|View full text |Cite
|
Sign up to set email alerts
|

A toolkit for rapid gene mapping in the nematode Caenorhabditis briggsae

Abstract: BackgroundThe nematode C. briggsae serves as a useful model organism for comparative analysis of developmental and behavioral processes. The amenability of C. briggsae to genetic manipulations and the availability of its genome sequence have prompted researchers to study evolutionary changes in gene function and signaling pathways. These studies rely on the availability of forward genetic tools such as mutants and mapping markers.ResultsWe have computationally identified more than 30,000 polymorphisms (SNPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…Moreover, the deep split of "Kerala" strains from all other C. briggsae lineages approximately 2 million generations ago (∼200 kya), averaging 1.2% silent-site sequence divergence, is an especially striking feature of the evolutionary history of this species. This splitting reinforces a key role for C. briggsae in studying adaptive divergence (Prasad et al 2011) and incipient speciation (Dolgin et al 2008;Ross et al 2011;Baird and Stonesifer 2012), by exploiting available genetic toolkits (Koboldt et al 2010;Ross et al 2011;Frøkjaer-Jensen 2013), and the genomic resource provided here.…”
Section: Wwwgenomeorgsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, the deep split of "Kerala" strains from all other C. briggsae lineages approximately 2 million generations ago (∼200 kya), averaging 1.2% silent-site sequence divergence, is an especially striking feature of the evolutionary history of this species. This splitting reinforces a key role for C. briggsae in studying adaptive divergence (Prasad et al 2011) and incipient speciation (Dolgin et al 2008;Ross et al 2011;Baird and Stonesifer 2012), by exploiting available genetic toolkits (Koboldt et al 2010;Ross et al 2011;Frøkjaer-Jensen 2013), and the genomic resource provided here.…”
Section: Wwwgenomeorgsupporting
confidence: 73%
“…These features make C. briggsae a powerful tool for dissecting evolutionary pattern and process in connection with trait divergence in nature, especially in combination with its deep experimental toolkit (Koboldt et al 2010;Ross et al 2011;Frøkjaer-Jensen 2013). Indeed, this species is now an active target of research into the molecular basis of trait variation and adaptation (Baird et al 2005;Prasad et al 2011;Ross et al 2011;Stegeman et al 2013), the evolution of development (Delattre and Félix 2001;Hill et al 2006;Guo et al 2009;Marri and Gupta 2009), and speciation (Woodruff et al 2010;Baird and Stonesifer 2012;Kozlowska et al 2012;Yan et al 2012).…”
mentioning
confidence: 99%
“…As an emerging model for determining the genetic basis of phenotypic variation (Baird et al, 2005;Hillier et al, 2007;Ross et al, 2011;Koboldt et al, 2010), these data further position C. briggsae as a model system for the genetic analysis of complex behavioural traits. We compared genetic backgrounds for the ability to perform thermotaxis and isothermal tracking within and between species by assaying 15 natural isolate strains of C. briggsae alongside two C. elegans strains, and demonstrated that C. briggsae can sense and navigate a thermal landscape in a manner similar to C. elegans.…”
Section: Discussionmentioning
confidence: 86%
“…Caenorhabditis briggsae is morphologically very similar to C. elegans, sharing a common life cycle and similar androdioecious sexual system (Nigon and Dougherty, 1949;Baird, 2001), but C. briggsae exhibits greater molecular differentiation among wild strains that might, in turn, underlie higher phenotypic variation (Cutter et al, 2006). As more genetic tools become available in C. briggsae, it is quickly catching up to C. elegans as a model system in its own right (Koboldt et al, 2010;Ross et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When we compared our C. briggsae gene assignments to the current WormBase assignment [based on a high-density recombination map (Hillier et al 2007;Koboldt et al 2010;Ross et al 2011)] we found that we correctly assigned 236 of 236 contigs to autosomes and 27 of 28 contigs to the X chromosome ( Figure 1D). The inconsistent contig, cb25.…”
Section: Resultsmentioning
confidence: 96%